The solution of a one-phase Stefan problem with a forcing term by homotopy analysis method - Onyejekwe, Ogugua (International Journal of Advanced Mathematical Sciences, 2014)
In this paper, we use the homotopy analysis method (HAM), to obtain the solutions of the temperature distribution, the position of the moving boundary and the Stefan condition. There are advantages to using HAM, firstly it is independent of small/large physical parameters, there is flexibility on the choice of base function and initial guess of solution and lastly there is great generality. The results obtained from this method shows high accuracy, computational efficiency and a strong rate of convergence. Keywords: Dirichlet; Forcing Term; Homotopy Analysis Method; Stefan Problem.